CRISPR/Cas9 RET Gene Knockout in Medullary Thyroid Carcinoma Cell-lines: Optimization and Validation - Marjan Zarif-Yeganeh; Dariush D Farhud; Azam Rahimpour; Sara Sheikholeslami; Setareh Shivaei; Mehdi Hedayati (Tehran University of Medical Sciences, 2022)
Background: Medullary Thyroid Cancer (MTC) is a very aggressive type of thyroid carcinoma. Mutation in RET proto-oncogene is demonstrated in MTC development. We aimed to knock-out of RET-oncogene using CRISPR/Cas9 genome editing method in MTC cell-lines. Methods: This research was conducted in Shahid Beheshti University of Medical Sciences, Tehran, Iran during 2019-2020. Four different sgRNAs were designed to target exons one, two, and four of RET-oncogene in TT and MZ-CRC-1 cell-lines using bioinformatics tools, then the CRISPR/Cas9 constructs was made. About 72-hours after cell transfection, T7EI method and DNA sequencing were used to confirm the knock-out of RET-oncogene. Expression of RET, Calcitonin genes and RET protein were evaluated by Real-time PCR and ELISA, respectively. Results: The results of T7E1, and DNA sequencing of transfected cells confirmed RET gene knock-out by CRISPR/Cas9. There was a significant decrease in RET gene expression and RET protein in transfected TT and MZ cells compared to controls. The rate of cell apoptosis in transfected cells was significantly increased. Calcitonin gene expression was also significantly reduced in transfected cells. p-RET, p-PI3K, p-AKT, p-MEK, p-ERK protein levels were significantly reduced in TT and MZ transfected cells. Conclusion: For the first time, knock-out of RET gene was performed and confirmed using CRISPR/Cas9. Inhibition of this gene leads to inhibition of the tyrosine kinase RET signal transduction pathway. Therefore, it can be one of the most effective and specific therapeutic goals in the field of Personalized Medicine in the treatment of diseases caused by over activity of RET molecular pathway.